Cooperative effects of sequential PGF2α and IL-1β on IL-6 and COX-2 expression in human myometrial cells†. Issue 5 (22nd February 2019) - Leimert, Kelycia B; Verstraeten, Barbara S E; Messer, Angela; Nemati, Rojin; Blackadar, Kayla; Fang, Xin; Robertson, Sarah A; Chemtob, Sylvain; Olson, David M
Abstract: The change from the state of pregnancy to the state of parturition, which we call uterine transitioning, requires the actions of inflammatory mediators and results in an activated uterus capable of performing the physiology of labor. Interleukin (IL)-1β and prostaglandin (PG)F2α are two key mediators implicated in preparing the uterus for labor by regulating the expression of uterine activation proteins (UAPs) and proinflammatory cytokines and chemokines. To investigate this process, primary human myometrial smooth muscle cells (HMSMC) isolated from the lower segment of women undergoing elective cesarean sections at term (not in labor) were used to test the inflammatory cytokine and UAP outputs induced by PGF2α and IL-1β alone or in sequential combinations. PGF2α and IL-1β regulate mRNA abundance of the PGF2α receptor FP, the IL-1 receptor system, interleukin 6, and other UAPs ( OXTR, COX2 ), driving positive feedback interactions to further amplify their own proinflammatory effects. Sequential stimulation of HMSMC by PGF2α and IL-1β in either order results in amplified upregulation of IL-6 and COX-2 mRNA and protein, compared to their effects individually. These profound increases were unique to myometrium and not observed with stimulation of human fetal membrane explants. These results suggest that PGF2α and IL-1β act cooperatively upstream in the birth cascade to maximize amplification of IL-6 and COX-2, to build inflammatory load and thereby promote uterine transition. Targeting PGF2α or IL-1β, their actions, or intermediates (e.g. IL-6) would be an effective therapeutic intervention for preterm birth prevention or delay. Abstract : PGF2α and IL-1β act cooperatively upstream in the birth cascade to maximize amplification of IL-6 and COX-2, contributing to increased inflammatory burden and promoting uterine transition.